The Influence of Corporate Social Responsibility and Good Corporate Governance on Market Response with Corporate Reputation as a Moderator - Makhmudah, Syahriyatul; Jariah, Ainun; Fadah, Isti; Kasno, Kasno (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2026)
This study examines the impact of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on market response, with corporate reputation as a moderating variable. The research focuses on property sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, using a purposive sample of 13 firms. A quantitative approach is employed, applying multiple linear regression and moderated regression analysis (MRA) to test both direct and interaction effects. CSR is measured based on disclosures aligned with Global Reporting Initiative (GRI) indicators and Financial Services Authority (POJK) regulations, while GCG is proxied by managerial ownership. Market response is assessed using cumulative abnormal return (CAR), and corporate reputation is evaluated through indicators of public visibility and corporate image. The findings reveal that CSR has a positive and significant effect on market response, indicating that social responsibility disclosures provide favorable signals to investors. Conversely, GCG does not significantly influence market response, suggesting that governance mechanisms have not yet become a primary consideration for investors in the property sector. Corporate reputation is found to strengthen the relationship between CSR and market response, but it does not moderate the relationship between GCG and market response. These results highlight the strategic role of corporate reputation in enhancing the market impact of CSR activities. The study contributes to the development of legitimacy and agency theories in the Indonesian capital market and provides practical implications for companies, regulators, and investors in integrating non-financial information into investment and governance decisions